Communitarian radio building Social Capital: rural women in radio production - Lima, Ivanice Oliveira de (2012)
The study analyzes the production of the Alternativa FM Communitarian Radio by the women involved in the actions of the non-governmental organization Nazaré da Mata Women Association – Amunam. The focus is how Alternativa FM contributes for the development of the human and social capitals of these women. This Radio Station is related to the human capital construction, through an educational effort in the female broadcaster´s technical abilities formation; and the social capital’s, as the work in the radio station stimulates contribution and political participation of these women who are involved in the radio practice.